Investigating kinship of Neolithic post-LBK human remains from Krusza Zamkowa, Poland using ancient DNA. (January 2017) - Juras, Anna; Chyleński, Maciej; Krenz-Niedbała, Marta; Malmström, Helena; Ehler, Edvard; Pospieszny, Łukasz; Łukasik, Sylwia; Bednarczyk, Józef; Piontek, Janusz; Jakobsson, Mattias; Dabert, Miroslawa
Highlights: HID-Ion AmpliSeq™ Identity panel and mtDNA genomes were used to establish kinship. Woman and child from double grave and adjacent child were not maternally related. Funeral rites in Neolithic Lengyel societies could rely on non-biological kinship. HID-Ion AmpliSeq™ Identity panel was useful only in well preserved DNA samples. Abstract: We applied an interdisciplinary approach to investigate kinship patterns and funerary practices during the middle Neolithic. Genetic studies, radiocarbon dating, and taphonomic analyses were used to examine two grave clusters from Krusza Zamkowa, Poland. To reconstruct kinship and determine biological sex, we extracted DNA from bones and teeth, analyzed mitochondrial genomes and nuclear SNPs using the HID-Ion AmpliSeq™ Identity panel generated on Illumina and Ion Torrent platforms, respectively. We further dated the material (AMS 14 C) and to exclude aquatic radiocarbon reservoir effects, measures of carbon and nitrogen stable isotopes for diet reconstruction were used. We found distinct mitochondrial genomes belonging to haplogroups U5b2a1a, K1c and H3d in the first grave cluster, and excluded maternal kin patterns among the three analyzed individuals. In the second grave cluster one individual belonged to K1a4. However, we could not affiliate the second individual to a certain haplogroup due to the fragmented state of the mitochondrial genome. Although the individuals from the second grave cluster differ at position 6643, we believe that more data is needed to fully resolve this issue. We retrieved between 26 and 77 autosomal SNPs from three of the individuals. Based on kinship estimations, taking into account the allelic dropout distribution, we could not exclude first degree kin relation between the two individuals from the second grave cluster. We could, however, exclude a first degree kinship between these two individuals and an individual from the first grave cluster. Presumably, not only biological kinship, but also social relations played an important role in the funerary practice during this time period. We further conclude that the HID-Ion AmpliSeq™ Identity Panel may prove useful for first degree kin relation studies for samples with good DNA preservation, and that mitochondrial genome capture enrichment is a powerful tool for excluding direct maternal relationship in ancient individuals.